Corner's rules pass the test of time: little effect of phenology on leaf–shoot and other scaling relationships. (29th June 2020) - Fajardo, Alex; Mora, Juan P; Robert, Etienne
Abstract: Background and Aims: Twig cross-sectional area and the surface area of leaves borne on it are expected to be isometrically correlated across species (Corner's rules). However, how stable this relationship remains in time is not known. We studied inter- and intraspecific twig leaf area–cross-sectional area ( l a – c s ) and other scaling relationships, including the leaf–shoot mass ( l m – s m ) scaling relationship, across a complete growing season. We also examined the influence of plant height, deciduousness and the inclusion of reproductive buds on the stability of the scaling relationships, and we discuss results from a functional perspective. Methods: We collected weekly current-year twigs of six Patagonian woody species that differed in growth form and foliar habit. We also used prominent inflorescences from Embothrium coccineum (Proteaceae) to assess whether reproductive buds alter the l a – c s isometric relationship. Mixed effects models were fitted to obtain parameter estimates and to test whether interaction terms were non-significant (invariant) for the scaling relationships. Key Results: The slope of the l a – c s scaling relationship remained invariant across the growing season. Two species showed contrasting and disproportional (allometric) l a – c s scaling relationships (slope ≠ 1). Scaling relationships varied significantly across growth form and foliar habit. The l m – s m scaling relationship differed between reproductive- and vegetative-origin twigs in E. coccineum, which was explained by a significantly lower leaf mass per area in the former. Conclusions: Although phenology during the growing season appeared not to change leaf–shoot scaling relationships across species, we show that scaling relationships departed from the general trend of isometry as a result of within-species variation, growth form, foliar habit and the type of twig. The identification of these functional factors helps to understand variation in the general trend of Corner's rules.